(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
As for the research goals, they focused on developing specific exercises to develop the speed of the kinematic response and the accuracy of receiving service of volleyball, and to know the effect of these exercises in developing the speed of motor response and the accuracy of the receiving service for students of volleyball, this research was conducted on a sample of (12) medium-fat students, who were divided into two equal groups, one experimental and the other control, each group consisting of (6) students, after conducting the processes of homogeneity and parity, The appropriate tests for this skill were also chosen, with an exploratory experiment conducted on a group of medium-fat volleyball students from outside the basic research sample with the use of tools and aids in the research, pre-tests were conducted on the two groups, and then the vocabulary of specific exercises was applied within the educational units of (16) educational units. The time of each unit is (90) minutes by two units per week, the share of exercises within the main section of the educational unit was (30) minutes, the end of the educational units for this skill, the post tests were taken, and then treating the results of the research using appropriate statistical means. The two researchers came up with several conclusions, the most important of which was that the vocabulary of the specific exercises that were used had a positive effect on developing the speed of motor response and the accuracy of receiving service e volleyball.